Supported Palladium Nanoparticles Catalyzed Intermolecular Carbopalladation of Nitriles and Organoboron Compounds - Liu, Xin; Liu, Dan; Muschin, Tegshi; Bao, Agula; Bai, Chaolumen; Bao, Yong-Sheng (Frontiers in Chemistry, 2022)
The first heterogeneous catalyzed example for the direct synthesis of aromatic ketones via intermolecular carbopalladation of aliphatic nitriles and organoboron compound was developed. This mild method proceeds with supported palladium nanoparticles catalyst that could be reused and recycled five times. The fresh and used catalysts was characterized by XPS and TEM. The XPS analysis indicated that Pd0 was active species for the reaction. This methodology provides a mild and cost-effective strategy for the efficient synthesis of ketones.